PENINGKATAN HASIL BELAJAR MATEMATIKA SIFAT UNSUR BANGUN RUANG DAN SIMETRI MELALUI METODE INQUIRY - a.rofik a.rofik (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2017)
The study was aimed to describe the improvement of mathematics learning outcomes in the element properties of Build Space and Symmetry using inquiry method at the sixth A graders of state elementary school Rejosari. The study was designed in a Class Action Research (PTK) within 2 cycles. Each cycle consisted of four stages, namely action planning, action, evaluation, and reflection. Reflection activity was done with peers (collaborative partners). The instrument used was a written test in the form of worksheets. Through the application of Inquiry method supported by relevant media appeared to have a positive impact, which can increase student motivation and learning outcomes in the properties of the Elements Build Space and Symmetry material. It showed the students’ learning mastery. That proof can be observed from the results of the percentage of each cycle, i.e 60% in the first cycle and 79.50% in the second cycle. Thus, the application of Inquiry method can improve learning outcomes Mathematical properties of Elements Build Space and Symmetry material.